Country-level fire perimeter datasets (2001–2021) - Adam L. Mahood; Estelle J. Lindrooth; Maxwell C. Cook; Jennifer K. Balch (Scientific Data, 2022)
Measurement(s) Fire event occurrence • growth rate • size Technology Type(s) Satellite fire detections Sample Characteristic - Environment fire Sample Characteristic - Location global